Changes in body composition and meat quality in response to dietary amino acid provision in finishing broilers. (5th October 2018) - Belloir, P.; Lessire, M.; Lambert, W.; Corrent, E.; Berri, C.; Tesseraud, S.
Abstract : In order to control and optimize chicken quality products, it is necessary to improve the description of the responses to dietary amino acid (AA) concentration in terms of carcass composition and meat quality, especially during the finishing period. The aim of this study was to investigate the effects of Lysine (Lys, i.e. a limiting AA used as reference in AA nutrition) and AA other than Lys (AA effect). In total, 12 experimental diets were formulated with four levels of digestible Lys content (7, 8.5, 10 and 11.5 g/kg) combined with either a low (AA−), adequate control (AAc) and high (AA+) amount of other essential AA (EAA) expressed as a proportion of Lys. They were distributed to male Ross PM3 from 3 to 5 weeks of age. No significant AA×Lys interaction was found for growth performance or carcass composition. Body weight and feed conversion ratio were significantly improved by addition of Lys but were impaired in broilers receiving the AA− diets, whereas breast meat yield and abdominal fat were only affected by Lys. No additional benefit was found when the relative amount of other EAA was increased. There was a significant AA×Lys interaction on most of the meat quality traits, including ultimate pH, color and drip loss, with a significant effect of both AA and Lys. For example, AA− combined with reduced Lys level favored the production of meat with high ultimate pH (>6.0), dark color and low drip loss whereas more acid, light and exudative meat (<5.85) was produced with AA+ combined with a low Lys level. In conclusion, growth performance, carcass composition and meat quality are affected by the levels of dietary Lys and AA in finishing broilers. In addition, interactive responses to Lys and AA are found on meat quality traits, leading to great variations in breast pHu, color and drip loss according AA balance or imbalance.